2021
DOI: 10.1016/j.clinthera.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mortality After Oral Polio Vaccination and Increased Mortality After Diphtheria-tetanus-pertussis Vaccination in Children in a Low-income Setting

Abstract: Purpose: The diphtheria-tetanus-pertussis vaccine (DTP) and oral polio vaccine (OPV) were introduced in children 3 of 5 months of age in 1981e1983 in Bandim, in the capital of Guinea-Bissau. Because DTP has been linked to deleterious nonspecific effects (NSEs) and OPV to beneficial NSEs, we followed up this cohort to 3 years of age and examined the effects of DTP with OPV on all-cause mortality and the interactions of DTP and OPV with the measles vaccine (MV). Methods: DTP and OPV were offered at 3 monthly com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Routine OPV could be assessed in 3 studies in which children received OPV-only because DTP was missing ( Table 1 ). OPV-only recipients had 3-fold lower all-cause mortality than recipients of DTP + OPV (relative risk [RR], 0.33 [95% CI, 0.14–0.75]) [ 17–20 ] in 2 studies when DTP and OPV were introduced in Guinea-Bissau in the 1980s. Twenty years later, DTP was missing for several months; the all-cause case fatality ratio (CFR) was 3-fold lower for hospitalized children who had received OPV1 only and not the recommended DTP1 + OPV1 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Routine OPV could be assessed in 3 studies in which children received OPV-only because DTP was missing ( Table 1 ). OPV-only recipients had 3-fold lower all-cause mortality than recipients of DTP + OPV (relative risk [RR], 0.33 [95% CI, 0.14–0.75]) [ 17–20 ] in 2 studies when DTP and OPV were introduced in Guinea-Bissau in the 1980s. Twenty years later, DTP was missing for several months; the all-cause case fatality ratio (CFR) was 3-fold lower for hospitalized children who had received OPV1 only and not the recommended DTP1 + OPV1 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“… a OPV in these periods would have been trivalent OPV. b Mogensen et al [ 21 ] overlaps with reference [ 17 ] as it covers the same cohort but only in the age group 3–5 months, where the study was a natural experiment with limited selection bias. c Reported, directly or inversed, in the original publication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was shown for Bacillus Calmette-Guerin (BCG, vaccine against tuberculosis) ( 8 , 9 ), live vaccine against measles ( 10 ), Oral Poliovirus Vaccine (OPV) ( 11 ), and some other vaccines ( 12 ). Their introduction was found to reduce the all-cause mortality in low-income countries ( 13 , 14 ) and infectious disease-related hospitalizations in high-income countries ( 15 ). A prospective clinical study conducted in the Soviet Union in the late 1960s demonstrated that OPV could reduce the incidence of influenza and other acute respiratory diseases ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%